No additional long-term effect of group vs individual family intervention in the treatment of childhood obesity - A randomised trial - Kokkvoll, Ane Sofie; Grimsgaard, Sameline; Flægstad, Trond; Andersen, Lars Bo; Ball, Geoff; Wilsgaard, Tom; Njølstad, Inger (Acta Paediatrica, 2019)
Aim - Long‐term evaluations of childhood obesity treatments are needed. We examined changes in weight and cardiometabolic risk 1 year after children completed individual family or group‐based weight management interventions. Methods - In 2009‐2010, 6‐ to 12‐year‐old children with overweight or obesity from Finnmark and Troms (Norway) were recruited after media coverage and randomised to 24 months of individual family (n = 49) or group intervention (n = 48). Individual family intervention included counselling by a paediatric hospital team and a public health nurse in the local community. Group intervention included meetings with other families and a multidisciplinary hospital team, weekly physical activity sessions and a family camp. The primary outcome body mass index (BMI) and cardiometabolic risk factors were analysed 12 months after intervention. Results - From baseline to 36 months, children's BMI increased 3.0 kg/m 2 in individual family and 2.1 kg/m 2 in group intervention (between‐group −0.9kg/m 2 , P = 0.096). Data were available from 62 children (64%). Between‐group differences in C peptide ( P = 0.01) were detected in favour of group intervention. Pooled data from both treatment groups showed continued decrease in BMI standard deviation score ( P < 0.001). Conclusion - No between‐group difference in BMI was observed 12 months after intervention. Both groups combined showed sustained decrease in BMI standard deviation score.